Rezension von: Kroener, Bernhard R., Pröve, Ralf (Hrsg.), Krieg und Frieden - Maisch, Andreas (Württembergisch Franken, 1999)
Bernhard R. Kroener, Ralf Pröve (Hrsgg.), Krieg und Frieden. Militär und Gesellschaft in der Frühen Neuzeit, Paderborn (Ferdinand Schöningh) 1996. 353 S.